Robust Filtering and Fault Detection for T-S Fuzzy Systems - Wang, Xiao-Lei; Yang, Guang-Hong; Wang, Yu-Long (Springer Nature Singapore : Imprint: Springer, 2025)
XI, 148 p. 48 illus., 43 illus. in color.